1996
DOI: 10.1111/j.1476-5381.1996.tb15536.x
|View full text |Cite
|
Sign up to set email alerts
|

The activation of P1‐ and P2‐purinoceptors in the guinea‐pig left atrium by diadenosine polyphosphates

Abstract: 1 The effects of P', P2-di(adenosine) pyrophosphate (AP2A), P',P3-di(adenosine) triphosphate (AP3A), P',P"-di(adenosine) tetraphosphate (AP4A), P',P5-di(adenosine) pentaphosphate (AP5A), ATP, a,,Bmethylene ADP and 2-chloroadenosine (2-ClAd) were examined in the guinea-pig driven left atrium.2 All these purine compounds except a,#-methylene ADP produced a negative inotropic response with a rank order of potency of: 2-ClAd > > AP2A > ATP > AP4A = AP3A = AP5A. The ECs, value for 2-ClAd was approximately 1 guM, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…Hoyle (1990) proposed that diadenosine polyphosphates interact with receptors distinct from P1-and Pµ-purinoceptors, yet studies using intact preparations suggest that some of the effects of diadenosine polyphosphates are mediated by purinoceptors. Hoyle et al (1996) reported that the negative inotropic responses of guinea-pig left atria to diadenosine polyphosphates are mediated by P1-and Pµ-purinoceptors. In the rat, the responses to APÛA were shown to involve P1-purinoceptors (Kengatharan et al 1994), while the responses of isolated human and guinea-pig ventricular preparations to APÜA appear to involve P1-purinoceptors (Vahlensieck et al 1996).…”
Section: Diadenosine Polyphosphatesmentioning
confidence: 99%
“…Hoyle (1990) proposed that diadenosine polyphosphates interact with receptors distinct from P1-and Pµ-purinoceptors, yet studies using intact preparations suggest that some of the effects of diadenosine polyphosphates are mediated by purinoceptors. Hoyle et al (1996) reported that the negative inotropic responses of guinea-pig left atria to diadenosine polyphosphates are mediated by P1-and Pµ-purinoceptors. In the rat, the responses to APÛA were shown to involve P1-purinoceptors (Kengatharan et al 1994), while the responses of isolated human and guinea-pig ventricular preparations to APÜA appear to involve P1-purinoceptors (Vahlensieck et al 1996).…”
Section: Diadenosine Polyphosphatesmentioning
confidence: 99%
“…In anesthetized dogs and pigs, Ap4A caused a decrease in mean arterial pressure [12,13] which we demonstrated recently also for Ap4A, Ap5A and Ap6A [14]. Diadenosine polyphosphates induce negative chronotropic and inotropic responses in guineapig, canine, and human cardiac preparations [1,6,12]. The vascular tone in several organs is influenced by diadenosine polyphosphates.…”
Section: Introductionmentioning
confidence: 99%
“…The diadenosine polyphosphates have recently received considerable attention due to their cardiovascular effects [1][2][3][4][5][6]. Members of this class of compounds consist of two adenosine moieties connected via 5)-ribose linkage to each end of a polyphosphate chain.…”
Section: Introductionmentioning
confidence: 99%
“…Diadenosine polyphosphates (AP nA) represent a group of platelet and chromaffin cell-derived mediators with various effects in the cardiovascular system. In multicellular preparations of the heart their actions resemble those of adenosine (Ado) and are sensitive to Al receptor antagonists (Hoyle et al 1996;Vahlensick et al 1996). We have studied AP nA (n = 4-6) in isolated atrial myocytes by measuring G protein-gated IK(ACh)' an established target of Al receptors.…”
Section: University Of L Eeds Uk and Nagoya University Japanmentioning
confidence: 99%